Aeroelastic analysis of super long cable-supported bridges - Zhang, Xin (2008)
A study on properties of interactive wind forces on bridge sectional models is presented in this thesis. Two and three-dimensional sectional model tests in the wind tunnel were carried out to detect nonlinearity in the self-excited wind forces. The transformation of a frequency-time domain hybrid flutter derivative model to either time or frequency domain usually requires the linearity assumption of the self-excited wind forces, which has not been investigated thoroughly.